Perfect motherhood : science and childrearing in America - Apple, Rima D. (Rima Dombrow), 1944- (Rutgers University Press, 2006)
Parenting today is virtually synonymous with worry. We want to ensure that our children are healthy, that they get a good education, and that they grow up to be able to cope with the challenges of modern life. In our anxiety, we are keenly aware of our inability to know what is best for our children. When should we toilet train? What is the best way to encourage a fussy child to eat? How should we protect our children from disease and injury?Before the nineteenth century, maternal instinct--a mother's "natural know-how"--was considered the only tool necessary for effective childrearing. Over the past two hundred years, however, science has entered the realm of motherhood in increasingly significant ways. In Perfect Motherhood, Rima D. Apple shows how the growing belief that mothers need to be savvy about the latest scientific directives has shifted the role of expert away from the mother and toward the professional establishment. Apple, however, argues that most women today are finding ways to negotiate among the abundance of scientific recommendations, their own knowledge, and the reality of their daily lives.